A Novel Digital Templating Methodology for Arthroplasty: Experience from Patients with Osteonecrosis of the Femoral Head. Issue 1 (January 2017) - Dong, Ning; Yang, Chen; Li, Shu-Qiang; Gao, Yu-Hang; Liu, Jian-Guo; Qi, Xin
Purpose: To assess the accuracy of a novel digital templating methodology for total hip arthroplasty (THA) in patients with osteonecrosis of the femoral head (ONFH). Methods: A retrospective study was carried out on 77 hips in 58 patients who had undergone uncemented THA for ONFH. Pre-Operative radiographs were templated using a 2-step procedure: (i) calculation of basic cup and stem sizes based on the anatomical morphology; (ii) adjustment of the basic sizes to account for variables such as femoral external rotation, osteoporotic changes in the femur, osteosclerotic changes in the acetabulum, and the type of stem. Basic and adjusted sizes were compared with the actual sizes of the implants used. Results: Before adjustment, the overall accuracy was 69% and 70% for stem size and the cup respectively. Among all the cases, 31 femoral components (40%) and 17 acetabular components (22%) required adjustment. After adjustment, the accuracy of templating for stem and cup sizes in these adjusted cases improved from 52% to 87% (p = 0.002), and 41% to 82%, respectively (p = 0.032). And the overall templating accuracy improved to 83% on the stem side (p = 0.038) and 79% on the cup side (p = 0.195). Conclusions: Pre-Operative digital templating was useful in predicting cup and stem sizes in patients with ONFH. Radiographic signs of femoral rotation or osteoporotic changes call for appropriate adjustment to improve the accuracy of templating for THA.